Weathering the storm: precipitation whiplash has limited effects on agricultural production and pesticide use in California - Ashley E Larsen; Daniel Sousa; Amy Quandt; Andrew J MacDonald (Environmental Research Letters, 2025)
Fluctuations in extreme weather such as a shift from an extreme dry to an extreme wet year, termed hydroclimate volatility or precipitation whiplash, present potential challenges and opportunities for agricultural production in water-limited regions. Yet, whether the sudden profusion of precipitation or the presence of flooding has a net positive or negative impact on agricultural production, particularly agricultural pests, is understudied. Using a difference-in-difference approach applied to field-level pesticides from ∼13 000 field/y observations in Kern County, CA, we evaluate how precipitation whiplash impacted agricultural pest control. We show the wet year had an anticipated bump in pesticides targeting molds and weeds and an unanticipated decrease in insecticides. Yet, there was little effect of on-field standing water on pesticide use. County-wide crop statistics, available for a subset of crops, were also similar across years, with similar area harvested, yields and total value in the historically wet versus the prior dry year. Despite the historic nature of the drought and proceeding rainfall events, farmers, on average, appeared to adapt to precipitation whiplash successfully. Given the increasing prevalence of precipitation whiplash as well as policy efforts to increase groundwater recharge through on-field flooding in wet years, such null effects suggest the benefits to harnessing extreme precipitation do not imply major costs for pest control.